Brain machine interface: A comparison between fuzzy and neural classifiers - Hema, Chengalvarayan Radhakrishnamurthy; Paulraj, Murugesapandian; Ramachandran, Nagarajan; Sazali, Yaacob; Abdul Hamid, Adom (ICIC International, 2009)
Link to publisher's homepage at http://www.ijicic.org/